Tradisi Kepercayaan Mitos Naga Tahun Dalam Perkawinan Adat Perspektif Sosiologi Hukum Islam (Studi Kasus Di Kec. Maron Probolinggo) - Iroda Auliya; Abu Yazid Adnan Quthny; Ramdan Wagianto (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2025)
This article discusses the tradition of the Maron sub-district community's belief in marital taboos. The majority of people living in Maron Sub-district are Muslims, but they also believe in mystical things such as the myth of the dragon of the year which is believed to bring mudharat (death) to the bride and groom who violate it. The purpose of this study is to reinterpret the customs that developed in Maron Probolinggo sub-district. The method used is qualitative by using the sociology approach of Islamic law. The results of the author's research using Talcott Parsons' four AGIL imperatives approach, show that the Maron sub-district community still preserves the tradition of abstinence from the myth of the dragon of the year that has existed from ancestral times and from generation to generation. Various social structures or systems maintain equilibrium so that the tradition can still take place and survive until now. Furthermore, the values contained in the tradition are to seek benefits by avoiding taboos that are believed to cause harm. Therefore, I can conclude that the tradition is a valid 'urf whose existence can still be tolerated and practiced by the people of Maron Sub-district.